2019
DOI: 10.1021/acs.jpca.8b11342
|View full text |Cite
|
Sign up to set email alerts
|

Controlling NO Production Upon Valence Ionization of Nitroimidazoles

Abstract: Nitroimidazole exhibits a remarkable regioselective fragmentation subsequent to valence ionization, which is characterized by ejection of NO. As NO is also considered to be an effective radiosensitizer, we investigated its production efficiency as a function of isomeric composition (the site of the NO 2 nitro group). We observe strong dependence in the 8.6−15 eV binding energy range, and moreover, that the production of NO can be effectively suppressed by methylation of nitroimidazole. This behavior can be und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Bolognesi et al [39] report a strongly suppressed parent cation and a higher number and abundance of fragment cations. A recent PEPICO study of 2NI by Itälä et al [38] also reported the mass spectrum at the photon energy of 16 eV. The spectrum featured the parent cations, NO + and [2NI − NO] + , at m / z 83 as the strongest channels [38].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bolognesi et al [39] report a strongly suppressed parent cation and a higher number and abundance of fragment cations. A recent PEPICO study of 2NI by Itälä et al [38] also reported the mass spectrum at the photon energy of 16 eV. The spectrum featured the parent cations, NO + and [2NI − NO] + , at m / z 83 as the strongest channels [38].…”
Section: Resultsmentioning
confidence: 99%
“…A recent PEPICO study of 2NI by Itälä et al [38] also reported the mass spectrum at the photon energy of 16 eV. The spectrum featured the parent cations, NO + and [2NI − NO] + , at m / z 83 as the strongest channels [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the detailed mechanisms by which radiosensitisation operates are still unknown, it is believed that radiosensitisers are chemical compounds subject to redox reactions inside the hypoxic cells [4], and in case of nitroimidazoles, the ring facilitates reduction through reactive anion radicals' formation [5][6][7]. Nitroimidazole radiosensitisers have been thoroughly investigated by experimental methods on low-energy electron interactions [8][9][10][11][12] and together with nimorazole probed by electrospray ionization mass spectrometry [13][14][15]. While associative electron attachment may contribute to NIMO's radiosensitising effect, within the biological environment, electron transfer processes (redox reactions) may prevail and so these may seem more appropriate to describe the underlying molecular mechanisms of such chemical compounds and their role as radiosensitisers.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding positive ion formation of nimorazole and related compounds, we are aware of electrospray mass spectrometry experiments with nitroimidazolic compounds, 32,33 collision-induced dissociation of protonated nitroimidazoles, 34 nitroimidazole and imidazole ionization, 35,36 and the photofragmentation patterns of doubly ionized 4(5)-nitroimidazole and 1-methyl-5-nitroimidazole. 37 Yet, detailed knowledge on the appearance energies (AEs) of cations formed upon electron ionization of nimorazole is missing.…”
Section: Introductionmentioning
confidence: 99%